Defect-Induced π-Magnetism into Non-Benzenoid Nanographenes - Kalyan Biswas; Lin Yang; Ji Ma; Ana Sánchez-Grande; Qifan Chen; Koen Lauwaet; José M. Gallego; Rodolfo Miranda; David Écija; Pavel Jelínek; Xinliang Feng; José I. Urgel (Nanomaterials, 2022)
The synthesis of nanographenes (NGs) with open-shell ground states have recently attained increasing attention in view of their interesting physicochemical properties and great prospects in manifold applications as suitable materials within the rising field of carbon-based magnetism. A potential route to induce magnetism in NGs is the introduction of structural defects, for instance non-benzenoid rings, in their honeycomb lattice. Here, we report the on-surface synthesis of three open-shell non-benzenoid NGs (A1, A2 and A3) on the Au(111) surface. A1 and A2 contain two five- and one seven-membered rings within their benzenoid backbone, while A3 incorporates one five-membered ring. Their structures and electronic properties have been investigated by means of scanning tunneling microscopy, noncontact atomic force microscopy and scanning tunneling spectroscopy complemented with theoretical calculations. Our results provide access to open-shell NGs with a combination of non-benzenoid topologies previously precluded by conventional synthetic procedures.